Analyzing the Impact of Suburban Design Through a Comparison of Its Effects on the United States and France - Zervos, Konstantinos (Advances in Social Sciences Research Journal, 2025)
Suburban design shapes the way that people live and function globally on a daily basis. Despite its importance, people rarely consider the design choices around them and their impact. Recently, suburban sprawl has become omnipresent as the planning style has spread throughout rural landscapes and exurban areas. Through an analysis of suburban design, this paper scrutinizes suburban sprawl by considering its effect on the economy, environment, societal wellness, and social injustices in the United States and France. Overall, this research finds that suburban sprawl leads to an auto-centric and socially polarizing society, which negatively affects national well-being. This paper concludes by proposing possible solutions to suburban sprawl aimed at diversifying future building projects and limiting the nation’s reliance on automobiles.